Gamma secretase inhibitor impairs epithelial-to-mesenchymal transition induced by TGF-β in ovarian tumor cell lines. (15th January 2017) - Pazos, M.C.; Abramovich, D.; Bechis, A.; Accialini, P.; Parborell, F.; Tesone, M.; Irusta, G.
Abstract: Ovarian cancer is characterized by being highly metastatic, a feature that represents the main cause of failure of the treatment. This study investigated the effects of γ-secretase inhibition on the TGF-β-induced epithelial–mesenchymal transition (EMT) process in ovarian cancer cell lines. SKOV3 cells incubated in the presence of TGF-β showed morphological and biochemical changes related to EMT, which were blocked by co-stimulation with TGF-β and the γ-secretase inhibitor DAPT. In SKOV3 and IGROV1 cells, the co-stimulation blocked the cadherin switch and the increase in the transcription factors Snail, Slug, Twist and Zeb1 induced by TGF-β. DAPT impaired the translocation of phospho-β-catenin to the inner cell compartment observed in TGF-β-treated cells, but was not able to block the induction at protein level induced by TGF-β. Moreover, the inhibitor blocked the increased cell migration and invasiveness ability of both cell lines induced by TGF-β. Notch target genes (Hes1 and Hey1) were induced by TGF-β, decreased by DAPT treatment and remained low in the presence of both stimuli. However, DAPT alone caused no effects on most of the parameters analyzed. These results demonstrate that the γ-secretase inhibitor used in this study exerted a blockade on TGF-β-induced EMT in ovarian cancer cells. Highlights: TGF-β induced changes related to the EMT process in SKOV3 and IGROV1 cell lines. DAPT alone caused no effects on the cellular parameters analyzed related to the EMT process. DAPT exerted a blockade on TGF-β-induced EMT in ovarian cancer cell lines.